2014
DOI: 10.1080/03004430.2014.958482
|View full text |Cite
|
Sign up to set email alerts
|

The type of curriculum activities implemented in Jordanian preschools

Abstract: This study aimed to ascertain the nature of curriculum activities in Jordanian preschools. Fifteen preschools participated in the study. Data were collected by observing the children in their daily routines, as well as analysing their writings and drawings. Data were translated from Arabic to English before analysing it. Four main categories were identified from the data analysis process: academic learning experiences; daily routine; types of activities; children's artefacts. Analyses revealed that preschool e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ Despite the enormous budgets spent on these reforms, it was confined to specific aspects of teaching and learning science, such as supplementary materials, redesigning textbooks, and teachers' guides (Alhabahba et al, 2016), while little attention has been paid to conventional teaching practices that still dominates the minds of science teachers in Jordan (Abu Naba'h et al, 2009;Ahmad et al, 2015;Dagher & BouJaoude, 2011). The importance of the teaching methods used and the classroom climate lies in the fact that exposure to science can positively contribute to shaping students' attitudes towards science, as posited by (Hu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ Despite the enormous budgets spent on these reforms, it was confined to specific aspects of teaching and learning science, such as supplementary materials, redesigning textbooks, and teachers' guides (Alhabahba et al, 2016), while little attention has been paid to conventional teaching practices that still dominates the minds of science teachers in Jordan (Abu Naba'h et al, 2009;Ahmad et al, 2015;Dagher & BouJaoude, 2011). The importance of the teaching methods used and the classroom climate lies in the fact that exposure to science can positively contribute to shaping students' attitudes towards science, as posited by (Hu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When the international literature is examined, similar studies applied in different cultures areencountered . To cite an example, with the same purpose, the types of Jordanian preschool curriculum activities were assessed, and the results revealed that preschools emphasise academic experiences such as teaching children skills for reading and writing letters and some words in Arabic and English, as well as counting, and basic tenants of Islam, and do not focus as much on play time (Ahmad, Fayez, & Al-Zboon, 2015). On the other hand, Jayasuriya, Williams, Edwards and Tandon (2016) examined parents' perception of preschool activities regarding outdoor activities in the United States and found that although parents place importance on academics for their pre-schoolers, they also value and in fact demand for more outdoor time than the 60 min per day.…”
Section: Introductionmentioning
confidence: 99%